Neuroferritinopathy in a French family with late onset dominant dystonia - Chinnery, P F; Curtis, A R J; Fey, C; Coulthard, A; Crompton, D; Curtis, A; Lombés, A; Burn, J (Journal of medical genetics, 2003)
Key points We recently described a novel autosomal dominant basal ganglia disorder caused by an adenine insertion at position 460-461 of the gene for ferritin light polypeptide (FTL) in a large family from Cumbria in the north west of England. Table 1 Haplotypes of markers around the FTL mutation in affected subjects in the Cumbrian (UK) and French families Haplotypes Marker Linkage (cM)* Physical (Mb)[dagger] UK French D19S596 74.07 65.98 5 3 31598C - 66.03 5 6 REP9 - 66.04 3 6 REP8b - 66.16 5 4 REP8a - 66.16 4 2 FTL exon 4 mutation - 66.22 insA insA D19S879 75.41 66.31 3 3 HRC.PCR3 75.41 66.45 9 8 D19S604 75.41 66.69 2 4 D19S867 77.54 67.35 6 5 D19S866 77.54 67.59 9 2 *Marshfield genetic linkage map of chromosome 19: http://research.marshfieldclinic.org/genetics/ [dagger]UCSC Genome Browser (December 2001 freeze): http://genome.ucsc.edu/index.html DISCUSSION Here we describe the first non-British family with a mutation in the FTL gene causing neuroferritinopathy.